Health aspects of fat and cholesterol intake in everyday human nutrition - Belichovska Daniela, Pejkovski Zlatko, Silovska-Nikolova Aleksandra, Belichovska Katerina (Institute of Knowledge Menagament, Skopje, 2019)
Fat and cholesterol are an important group of nutrients that should be limited in the diet to reduce the risk of chronic diseases. Cardiovascular and carcinogenic diseases are associated with fat-rich diets, but also other chronic health problems can be exacerbated by high-fat diet. Recommendations promoted by the World Health Organization worldwide are reducing fat intake, primarily saturated fatty acids, trans-fatty acids and cholesterol as a way to minimize health risks. All of these recommendations, daily presented to the public, give consumers awareness to take care of their diet.
Keywords: fat, nutrition, health.